Visual Field Improvement After Pituitary Tumor Resection (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2022)
Background: Optic neuropathy due to chiasmal compressive lesion can affect the visual acuity, color vision, and visual field in both eyes. The most common visual field defect of chiasmal compression is a bitemporal hemianopia. Restoration of visual function is possible following surgical decompression. Purpose: To report a case of visual field improvement after pituitary tumor resection. Case Presentation: A 53 years old woman came with a chief complaint of blurred vision on her left eye since 3 months. Patient visual acuity was 0.25F1 on the right eye and counting fingers at 1 meter on the left eye. Ophthalmologic examination revealed optic disc pallor on both eyes. HVF 30-2 results showed bitemporal hemianopia. Head MRI with contrast showed an pituitary macroadema, size 2.3 x 2.2 x 2.7 cm and pushing the optic chiasm superiorly. Patient diagnosed with bilateral papil atrophy and bitemporal hemianopia caused by pituitary macroadenoma. She underwent endoscopic transsphenoidal tumor resection by a neurosurgeon. Visual function showed an improvement after 6 months follow up. Colour vision and contrast sensitivity were increased in left eye. HVF 30-2 showed visual field improvement in both eyes, especially in right eye. Conclusion: Pituitary adenoma can lead to visual impairment. Preoperative factors such as retinal nerve fiber layer thickness, severity of the preoperative deficit, duration of visual symptoms, tumor size, extent of resection, and patient age may also serve as predictors of postoperative visual outcomes..